AN EXTREMELY LARGE, CAULIFLOWER-TYPE, CUTANEOUS METASTASIS OF OVARIAN-CANCER ASSOCIATED WITH GOOD PROGNOSIS - Traiman, Paulo [UNESP]; Deluca, L. A.; Bacchi, C. E. (Academic Press Inc. Jnl-comp Subscriptions, 1994)
We report an unusual case of a 37-year-old woman who presented in 1980 with a serous papillary cystadenocarcinoma of the ovary. The patient refused any treatment and the patient was lost to follow-up for 6 years. After this period of time she returned with an extremely large, cutaneous, cauliflower-type of metastasis located in the lower abdominal wall and measuring 20 x 20 cm. She received two courses of chemotherapy treatment consisting of intraperitoneal cisplatin (100 mg/m2) and intravenous epirubicin (50 mg/m2) every 3 weeks. After the second course of chemotherapy she received cobalt radiotherapy (5000 cGy). Subsequently, she received four more courses of chemotherapy with dramatic remission of the cutaneous metastasis. Shortly after chemotherapy, the patient underwent a laparotomy consisting of the resection of the abdominal wall including the cutaneous metastasis completed by total abdominal hysterectomy, bilateral salpingo-oophorectomy, and omentectomy. The patient is well after the surgery and without any evidence of residual disease after 6 years of follow up. This description illustrates a rare example of ovarian cancer with skin metastases and favorable outcome. (C) 1994 Academic Press, Inc.